Weed Control in Pepper - William M. Stall (EDIS)
Revised! HS-199, a 5-page fact sheet by William M. Stall, guides Florida pepper growers in planning a weed-control program that integrates chemical, mechanical, and cultural methods to fit their weed problems and production practices. Published by the UF Department of Horticultural Sciences, May 2009.